Pertumbuhan Bibit Karet (Hevea brasiliensis Mull Arg.) Setelah Pemberian Beberapa Dosis Fungi Mikoriza Arbuskula (FMA) Indigineous Dari Hutan Pendidikan Dan Penelitian Biologi (HPPB) Universitas Andalas Padang - Akhyar Salim; Zozi Aneloi Noli; Suwirmen Suwirmen (Universitas Andalas, 2015)
An experimental study on the growth of rubber seedling (Hevea brasiliensis Mull Arg.) after inoculated with various doses of indigineous Arbuscular Mycorrizhal Fungy (AMF) from Biology Forest Research Center (FRCB) Andalas University Padang has been done from February to September 2013 in wire house and Plant Physiology Laboratory, Biology Department, Andalas University, Padang. The study aimed to find appropriate doses of indigineous Arbuscular Mycorrizhal Fungy (AMF) to growth rubber seedling. The experimental used Completely Randomized Design (CRD) with four treatments (control, 10, 20, and 30 g inoculants) and six replications. The results showed that 10 g inoculant gave significant effect to growth and dry weight of rubber stem due to high percentage of root infection. However rubber assosiatian with mycorrizha are less dependency. Keywords : rubber, AMF, inoculant, seedling growth